Littoral cell angioma: An incidental finding in a traumatic spleen - Madhurima Das; Rupsha Dutta Pal; Dwaipayan Samaddar; Jaya Bagchi Samaddar; Bidyut Krishna Goswami (Asian Journal of Medical Sciences, 2024)
Littoral cell angioma (LCA) of the spleen, a rare vascular tumor, is usually asymptomatic, often discovered incidentally and a majority of them are benign in nature. A 20-year-old boy with a history of blunt abdominal trauma, who underwent splenectomy showed the presence of a capsular tear and variegated outer surface on gross examination of the spleen. On the cut section, multiple nodular areas with areas of hemorrhage were noted. Microscopical examination revealed the proliferation of anastomosing, irregular, tortuous blood-filled channels with plenty of histiocytes in the splenic tissue and extensive areas of hemorrhage, inflammatory cell infiltration, and fibrinoid deposits. Immunohistochemistry revealed positivity for CD31 (endothelial differentiation), CD68, and lysozyme (histiocytic differentiation) but was negative for CD34. The final diagnosis was LCA in a case of ruptured spleen after ruling out angiosarcoma. The possibility of this benign entity to have contributed to the potentially fatal splenic injury cannot be overlooked.